Challenges and opportunities of micro online businesses - Maricon R. Angco, Khylle Xavier G. Bautista, Lovely Dannica S. Bituin, Gian Mae C. Manuel, Irene Mae O. Porras, Matthew Freddy A. Racadio, Glen Mark C. Ramos, Blesseree Joice L. Ruzol, Maria Audrey D. Sison 4 0 16; 5
u
Research Paper: (BSBA major in Business Economics) - Pamantasan ng Lungsod ng Maynila, 2021
Keywords: 2 -- 0; 6; 20; 20; 2